Sotalol Treatment may Interfere With Retrieval, Expression, and/or Reconsolidation Processes Thus Disrupting Traumatic Memories in a Post-Traumatic Stress Disorder Mice Model - Martinho, Raquel; Seixas, Rafaela; Azevedo, Márcia; Oliveira, Ana; Serrão, Paula; Moreira-Rodrigues, Mónica (Frontiers in Pharmacology, 2022)
The processes by which fear memory is encoded, consolidated, and re-consolidated are extremely complex and appear to require the release of stress hormones, especially adrenaline (AD). AD improves contextual fear memory, acting specifically on peripheral β2-adrenoceptors. Propranolol (peripheral and central β-adrenoceptor antagonist) treatment was shown to prevent post-traumatic stress disorder (PTSD) development and reduce its symptoms. However, propranolol has several side effects. Thus, we aimed to evaluate if sotalol (a peripheral β-adrenoceptor antagonist) treatment interferes with retrieval, expression, and/or reconsolidation of traumatic memories in a validated mice model that mimics the signs/symptoms of PTSD, thus intending to decrease them. Female mice were induced with PTSD following an established protocol. Sotalol (2.0 mg/kg) or vehicle were administered on days 2, 7, and 14. The percentage of freezing was calculated, and behavioral tests were carried out. Catecholamines in plasma were quantified by HPLC with electrochemical detection. Quantitative real-time polymerase chain reaction (qPCR) was used to evaluate mRNA expression of NR4A family genes in hippocampus. Following the submission of the animals to the same aversive context on days 2, 7, and 14, sotalol-treated mice exhibited significant less freezing behavior. In the elevated plus-maze test, the time spent and number of entries in the open arms, and total arm entries were increased in sotalol-treated mice. Also, the light-dark transition test revealed higher time spent, number of transitions to the light, and total number of transitions in sotalol-treated mice. Moreover, plasma AD was significantly decreased in sotalol-treated mice. On day 14, sotalol-treated mice exhibited a decrease in mRNA expression of Nr4a1 in the hippocampus. In conclusion, in PTSD mice model, sotalol appears to decrease traumatic memories and anxiety-like behavior, probably due to a decrease in peripheral adrenergic activity, which influences traumatic memories. The disruptive effects of sotalol upon re-exposure to the traumatic context may be consistent with interference in the retrieval, expression, and/or reconsolidation processes of contextual traumatic memory, resulting in a long-term reduction of PTSD symptoms and signs. The decreased Nr4a1 mRNA expression in the hippocampal formation may be crucial for these mice to develop diminished traumatic contextual memories after sotalol therapy in PTSD.